Cultivating Inclusive Classrooms: Equipping Pre-Service Teachers for Indigenous Language Integration (Teacher Education through Flexible Learning in Africa (TETFLE), 2025)
Research in South Africa shows that teacher education is often overlooked in language related studies, despite its central role in preparing educators for increasingly diverse classrooms shaped by migration and multilingualism. Many teachers report feeling inadequately prepared to respond to these realities, with monoglossic pedagogies persisting as a carry-over effect in higher education. This systematic review examined peer-reviewed studies published between 2020 and 2025, sourced from databases such as Scopus and Web of Science, and thematically analysed the evidence on how higher education institutions can better prepare teachers for culturally responsive teaching. Findings reveal that while multilingualism is the norm, relevant pedagogical strategies remain limited, leaving teachers under-equipped to meet learners’ needs and risking cognitive and equity gaps. The review highlights practical approaches for cultivating inclusive classrooms and offers recommendations for restructuring teacher education to foster competence in multilingual and culturally responsive pedagogy
Keywords: Culturally responsive pedagogy; Higher education; Multilingualism; Teacher education; Translanguaging